Upper limb treatment technigues for stroke survivors - Kornet, Martyna; Głowacka-Mrotek, Iwona; Nowacka, Krystyna; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Nowadays, the stroke is considered to be the main cause of acquired disability among adults in the world. Deficits occuring in the upper limb are its widespread consequence.The therapy of a paretic upper limb is the most difficult part of the rehabilitation process, and the recovery of the upper limb functions often takes place only at the final stage of the physiotherapy. The aim of this study is to present a variety of techniques to improve a post-stroke upper limb on the basis of the most recent literature. It was considered that the most important elements of the treatment used in the rehabilitation of the paretic upper limb are: exercise matching the anti-spasm pattern, maintaining appropriate position for exercise that provide an approximation of the shoulder joint and the use of cross-facilitation. The study indicates that the treatment of a post stroke upper limb should be based on the: physiotherapy, kinesiotherapy and specific positioning - all of them corresponding to a given stage of the disease. The work also presents the most frequently used methods, especially highlighting: the Prorioceptive Neuromuscular Facilitation (PNF), Bobath, Brunnstrom, CIMT and OIT. It was also shown that in order to enhance the effects of a post-stroke upper limb rehabilitation, it should be extended by modern methods such as Mirror Therapy, Virtual Reality or Robot-assisted Therapy.